“Making Space in Cyprus for Art and Activism”: An Interview with Ellada Evangelou - Leslie Frost (Université Toulouse - Jean Jaurès, 2021)
Interview with Ellada Evangelou. The interview occurred during preparations for the eighth annual Buffer Fringe Performing Arts Festival 2021 to be held October 8-10 in Nicosia, Cyprus.